2001
DOI: 10.1038/eye.2001.195
|View full text |Cite
|
Sign up to set email alerts
|

Pars plana vitrectomy with silicone oil in the management of combined rhegmatogenous retinal and choroidal detachment

Abstract: Results In a total of 10 eyes (77%) the first procedure produced anatomical success. Two eyes required a further procedure to achieve retinal reattachment, producing a final anatomical success rate of 92%. Patients with rhegmatogenous retinal detachment are occasionally found to have concurrent choroidal detachment (CD). These patients often present in an atypical way with pronounced uveitis, posterior synechiae, hypotony, deepened anterior chamber and pain. Patients with blue irides often have an apparent cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…2,16,17 Nevertheless, perioperative steroid has been widely used for preparation of surgery for RRD-CD patients. 2,[12][13][14][15]18,19 A short course of perioperative steroid may not be adequate in this regard as PVR formation is a continuing process after the surgery. 20 This may explain the findings in our study that preoperative steroid given about a week before surgery (PPV), in spite of regression of CD, appeared not to improve retinal reattachment rate, which is in agreement with a previous study before the era of PPV.…”
Section: Discussionmentioning
confidence: 99%
“…2,16,17 Nevertheless, perioperative steroid has been widely used for preparation of surgery for RRD-CD patients. 2,[12][13][14][15]18,19 A short course of perioperative steroid may not be adequate in this regard as PVR formation is a continuing process after the surgery. 20 This may explain the findings in our study that preoperative steroid given about a week before surgery (PPV), in spite of regression of CD, appeared not to improve retinal reattachment rate, which is in agreement with a previous study before the era of PPV.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Using this surgical technique, proliferative and concentrated vitreous can be excised, and all retinal holes can be identified. [ 6 8 ] However, the detachment recurrence rate remains high when vitrectomy is performed alone. Several studies investigating methods to improve anatomical outcomes have been performed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 23G PPV + phaco + capsulotomy without IOL implantation had a higher reattachment rate, which was approaching to rates previously reported in the literature. [ 4 – 6 ] Vitrectomy and capsulotomy may improve anterior and base vitrectomy, which may decrease anterior PVR. [ 13 , 14 ] A study by Tseng et al reported that pseudophakic eyes exhibited a higher proportion of hypotony after retinal reattachment surgery than eyes without IOL implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RRDCD is an uncommon type of retinal detachment, characterized by rapid progression, poor functional and anatomic prognosis due to the more difficult visualization of the ocular fundus and retinal breaks as well as the high rate of postoperative PVR development. [34][35][36] The reattachment rate of RRDCD treated by SB (35.5%-52.4%) was lower compared to that of RRD without CD, according to Seelenfreund et al [27] After the introduction of primary PPV, the reattachment rate of RRDCD improved by up to 90% [34][35][36].…”
Section: Preoperative Usementioning
confidence: 99%